THE IMPACT OF INADEQUATE LABORATORY PERSONNEL (LABORATORY HEADS, TECHNICIANS, AND ASSISTANTS) ON BIOLOGY PRACTICUM IMPLEMENTATION - Ana, Ana; Wulandari, Dhea Aprilia Ayu; Mafimudah, Rifatul; Sari, Fatma Mutia; Saifuddin, Much Fuad; Puspitasari, Etika Dyah (Prodi Pendidikan Biologi, FPMIPATI, Universitas PGRI Semarang, 2025)
This study aims to examine the limitations of human resources (HR) in school laboratories and their impact on the implementation of biology practicum activities at the senior high school level. A descriptive qualitative method was employed in Kotagede District, Yogyakarta, using purposive sampling to select two schools with active biology laboratories. Data were collected through in-depth interviews with laboratory personnel and biology teachers to explore the availability, involvement, and roles of laboratory staff in supporting practicum activities. The findings revealed significant differences between the two schools. School A had a complete laboratory staff, including a head of the laboratory and a laboratory assistant, which allowed practicum activities to be conducted in a structured and systematic manner, effectively supporting students' conceptual understanding and scientific understanding. supporting students' conceptual understanding and scientific skills. In contrast, School B lacked laboratory personnel, resulting in all practicum responsibilities being assigned to the biology teacher, which led to suboptimal implementation and limited student learning experiences. Therefore, efforts to increase the availability and competence of laboratory personnel in accordance with national standards are necessary. The presence of professional laboratory staff plays a crucial role in creating effective, meaningful, and skill-oriented biology learning through practicum-based approaches.